The application of the natural killer cells, macrophages and dendritic cells in treating various types of cancer - Helmin-Basa, Anna; Gackowska, Lidia; Balcerowska, Sara; Ornawka, Marcelina; Naruszewicz, Natalia; Wiese-Szadkowska, Małgorzata (Physical sciences reviews, 2022)
Innate immune cells such as natural killer (NK) cells, macrophages and dendritic cells (DCs) are involved in the surveillance and clearance of tumor. Intensive research has exposed the mechanisms of recognition and elimination of tumor cells by these immune cells as well as how cancers evade immune response. Hence, harnessing the immune cells has proven to be an effective therapy in treating a variety of cancers. Strategies aimed to harness and augment effector function of these cells for cancer therapy have been the subject of intense researches over the decades. Different immunotherapeutic possibilities are currently being investigated for anti-tumor activity. Pharmacological agents known to influence immune cell migration and function include therapeutic antibodies, modified antibody molecules, toll-like receptor agonists, nucleic acids, chemokine inhibitors, fusion proteins, immunomodulatory drugs, vaccines, adoptive cell transfer and oncolytic virus–based therapy. In this review, we will focus on the preclinical and clinical applications of NK cell, macrophage and DC immunotherapy in cancer treatment.